Collision dynamics of nanoscale Lennard-Jones clusters - Kalweit, Marco; Drikakis, Dimitris (American Institute of Physics (AIP), 2006)
An investigation of collision dynamics of nanoparticles for a broad range of impact factors and collision speeds is presented. The investigation is based on molecular dynamics simulations in conjunction with the Lennard-Jones interaction potential thus making the results applicable for a broad range of material properties. Identification criteria are used to classify the collision dynamics into different collision modes and submodes. Detailed analysis of the collision processes reveals the existence of coalescence and stretching separation modes, which are further classified according to their dynamics into sticking; slide-and-locking; droplet; normal stretching separation; stretching separation with satellite droplets; and shearing-off modes. Qualitative and quantitative comparisons with previous molecular dynamic studies and analytical prediction models derived for macroscopic droplet collisions are also discussed. The investigation reveals that the reflexive separation mode, which has been observed in macroscopic droplet collisions, does not occur for nanoparticles consisting of 10 000 (or less) atoms.